Student Centered Learning in Debate-Based Learning Perspective Surah An-Nahl Verse 125 - Cecep Sobar Rochmat; Jaziela Huwaida; Rosendah Dwi Maulaya; Bagus Asri Wibawa (Al-Hayat: Journal of Islamic Education, 2023)
This study aims to analyze the debate-based SCL learning model from the perspective of Surah An-Nahl verse 125. This research is vital because learning methods are one of the factors that determine learning success. One method of teaching approach that has proven to be effective and efficient is student-centred Learning (SCL). Development of learning with the SCL model, learners can more quickly understand the material and a teacher can more easily internalize educational values. If we analyze the interpretation of Surah An-Nahl verse 125, several education methods will be found. The type of research used is qualitative research with a library research approach. To analyze the data, this study used secondary data derived from the book of tafsir, which explains surah An-Nahl verse 125 and several data references related to the research. The results showed that SCL was learning in the surah An-Nahl verse 125 content, namely debate-based learning. The passage "refute them with a good rebuttal" signifies a debate learning method. With the jidal/debate method, at least two intelligences are formed in the learners. That is intellectual intelligence with broad insights to develop arguments and emotional intelligence necessary to maintain debate ethics. However, the debate set in education is undoubtedly a debate with polite words, full of ethics and does not put forward emotions. From the analysis of Surah An-Nahl verse 125, a teacher can apply the debate-based SCL learning model to improve the quality of his teaching.